Bone tissue, a new alternative in aggregates for concrete - Mora Samacá, Jaime Iván (Ingeniería Solidaria, 2019)
Introduction: The article bone tissue a new alternative in aggregates for concrete is the product of the research in process “Bone tissue in concrete”, carried out within the Civil Engineering program of the Piloto University since 2016. Antecedents: Observing performance studies and physical-mechanical properties of bone, this is identified as an appropriate material to be included in the mortar mix, which has been done since 2012 by some researchers, with results in favor of research.Methodology: The resistance and physical-mechanical properties of the bone tissue open a threshold of possibilities for its use within the concrete, which processed by means of calcination shows an alternative to be attached to the cement paste.Results: The compression tests in the cement paste, give favorable results replacing 10% the cementing material for bone calcined at 1200 ° C for one hour.Discussion: The bone tissue is apt to be used in different ways, within the mixture with a previous treatment.Conclusions: Calcined bone one hour at 1200 ° C has physical properties very similar to those of cement. The 10% Replacement generates greater resistance than the pure mixture.Originality: The treatment of the bone by means of calcination, varying the times and the temperature is an unprecedented method.Limitations: There is no standardization for bone element processing. Information about the subject is scanty with repetitive results.